A mesoscale modelling approach coupling SBFEM, continuous damage phase-field model and discrete cohesive crack model for concrete fracture. (1st February 2023) - Yu, Kelai; Yang, Zhenjun; Li, Hui; Tat Ooi, Ean; Li, Shangming; Liu, GuoHua
Highlights: A new numerical approach is developed for simulating complex 2D and 3D mesoscale fracture processes in concrete, by combing the scaled boundary finite element method (SBFEM), the continuous damage phase-field regularized cohesive zone model (PF-CZM) and the zero-thickness cohesive interface elements (CIEs). Using one SBFEM polygon or polyhedron to model one aggregate without internal nodal discretization saves considerable degrees of freedom (DOFs) compared with pure finite element models. No remeshing or pre-insertion of cohesive elements are needed to accommodate complicated crack propagation in the mortar. The approach is validated by a few 2D and 3D benchmark examples in mode-I and mixed-mode fracture. Abstract: This study develops an innovative numerical approach for simulating complex mesoscale fracture in concrete. In this approach, the concrete meso -structures are generated using a random aggregate generation and packing algorithm. Each aggregate is modelled by a single scaled boundary finite element method (SBFEM) based polygon with the boundary discretized only. The damage and fracture in the mortar is simulated by the continuous damage phase-field regularized cohesive zone model (PF-CZM), and the aggregate-mortar interfaces are modelled by zero-thickness cohesive interface elements (CIEs) with nonlinear softening separation-traction laws. This new approach thus takes full advantages of different methods, including the semi-analytical accuracy and high flexibility in mesh generation and transition of SBFEM, the mesh and length-scale independence of PF-CZM, and the ease-of-use of CIEs in modelling discrete interfacial fracture. These advantages are demonstrated by successful simulations of a few 2D and 3D benchmark examples in mode-I and mixed-mode fracture.